Ceramic composition and coil component
By using ceramic compositions of specific contents of Fe, Cu, Zn, Mn, Co, Ni, Y and Cr, the problem of the decrease in strength of the ceramic coil core under impact is solved, and a ceramic coil component with high initial and reheated flexural strength and insulation resistance is achieved.
Patent Information
- Application Number
- CN202411460155.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-31
- Filing Date
- 2024-10-18
- Publication Date
- 2025-05-02
AI Technical Summary
Existing ceramic coil cores are susceptible to impact during the transportation or polishing process, resulting in a decrease in strength, affecting the installation strength.
Using a ceramic composition containing Fe, Cu, Zn, Mn, Co, Ni, Y and Cr, by adjusting the content of these elements, the initial and reheated flexural strength of the ceramic composition is improved and the insulation resistance is enhanced.
The initial flexural strength of the ceramic composition and the flexural strength after reheating are achieved, while the insulation resistance is improved, ensuring high strength and high insulation performance of the coil components.
Smart Images

Figure CN119912248A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to ceramic compositions and coil components. Background Art
[0002] Patent document 1 discloses a winding type coil device using a drum core having a winding core and a flange portion. According to the coil device described in patent document 1, a first mounting protrusion formed on a flange portion at one end of the winding core portion and a second mounting protrusion formed on a flange portion at the other end of the winding core portion are arranged in an offset manner, so that the heat shock resistance is excellent.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-125397 Summary of the invention
[0006] Patent Document 1 describes that a drum core can be produced by molding and sintering a ferrite material such as Ni—Zn ferrite or Mn—Zn ferrite.
[0007] The manufacture of the drum core of the winding type coil device is usually to form and calcine the powder of the ferrite material to obtain a sintered body, and then further heat (reheat) the semi-finished product in order to bake the electrodes formed on the drum core legs. However, the drum core manufactured using the ferrite material described in Patent Document 1 has reduced strength due to impact during transportation or in additional processes such as drum polishing, and sometimes cannot obtain sufficient installation strength due to this influence.
[0008] The present invention is made to solve the above-mentioned problems, and its object is to provide a ceramic composition having high initial flexural strength and flexural strength after reheating and high insulation resistance. Furthermore, the present invention aims to provide a coil component having a ceramic core composed of the above-mentioned ceramic composition.
[0009] The ceramic composition of the present invention is a ceramic composition comprising Fe, Cu, Zn, Mn, Co, Ni, Y and Cr. When Fe, Cu, Zn, Mn, Co and Ni are converted into Fe2O3, CuO, ZnO, MnO, CoO and NiO respectively and the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO is set to 100 mol%, Fe is converted into Fe2O3 containing 41.9 mol% to 49.2 mol%, Cu is converted into CuO containing 4.4 mol% to 7.5 mol%, Zn is converted into CuO containing 10.5 mol% to 10.5 mol%, and Zn is converted into CuO containing 10.5 mol% to 10.5 mol%. n is converted into ZnO and contains 21.9 mol% to 36.0 mol%, Mn is converted into MnO and contains 0.043 mol% to 0.867 mol%, Co is converted into CoO and contains 0.0004 mol% to 1.2293 mol%, and Ni is contained as the remainder, and relative to 100 weight parts of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO, Y is converted into Y2O3 and contains 5 ppm to 800 ppm, and Cr is converted into Cr2O3 and contains 5 ppm to 800 ppm.
[0010] The coil component of the present invention includes a ceramic core composed of the ceramic composition of the present invention.
[0011] According to the present invention, a ceramic composition having high initial flexural strength and flexural strength after reheating and high insulation resistance can be provided. In addition, according to the present invention, a coil component having a ceramic core composed of the ceramic composition can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a front view schematically showing an example of the coil component of the present invention.
[0013] Figure 2 To schematically represent the composition Figure 1 A perspective view of an example of a ceramic core of a coil component is shown.
[0014] Explanation of symbols
[0015] 10 Coil components
[0016] 20 Ceramic core
[0017] 30 roll core
[0018] 31, 32 Main surface of the core
[0019] 33, 34 Side of the winding core
[0020] 40 flange
[0021] 41 Inner end surface of flange
[0022] 42 Outer end surface of flange
[0023] 43, 44 Side of flange
[0024] 45 Top surface of flange
[0025] 46 Bottom surface of flange
[0026] 50 terminal electrode
[0027] 55 wire
[0028] L Length direction
[0029] T height direction
[0030] WWidth direction DETAILED DESCRIPTION
[0031] Hereinafter, the ceramic composition and coil component of the present invention will be described.
[0032] However, the present invention is not limited to the following configurations, and can be appropriately changed and used within the scope of not changing the gist of the present invention. It should be noted that a combination of two or more of the preferred configurations of the present invention described below also belongs to the present invention.
[0033] [Ceramic composition]
[0034] The ceramic composition of the present invention contains Fe, Cu, Zn, Mn, Co, Ni, Y, and Cr. The ceramic composition of the present invention contains, for example, ferrite as a main component, preferably spinel ferrite as a main component.
[0035] In this specification, the ceramic composition refers to a sintered body, preferably a core-shaped sintered body. Therefore, in the ceramic composition of the present invention, the above atoms are mixed at the atomic level. That is, the ceramic composition of the present invention is synonymous with a ferrite sintered body.
[0036] The ceramic composition of the present invention converts Fe, Cu, Zn, Mn, Co and Ni into Fe2O3, CuO, ZnO, MnO, CoO and NiO respectively, and the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO is set to 100 mol%. Fe is converted into Fe2O3 and contains 41.9 mol% to 49.2 mol%, Cu is converted into CuO and contains 4.4 mol% to 7.5 mol%, Zn is converted into ZnO and contains 21.9 mol% to 36.0 mol%, Mn is converted into MnO and contains 0.043 mol% to 0.867 mol%, Co is converted into CoO and contains 0.0004 mol% to 1.2293 mol%, and Ni is contained as the remainder.
[0037] Furthermore, the ceramic composition of the present invention contains 5 ppm to 800 ppm of Y calculated as Y2O3 and 5 ppm to 800 ppm of Cr calculated as Cr2O3, relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO.
[0038] The ceramic composition of the present invention can improve the initial flexural strength and the flexural strength after reheating, and can also improve the insulation resistance by making the contents of Fe, Cu, Zn, Mn, Co, Ni, Y and Cr within the above ranges. For example, a ceramic composition having an initial flexural strength of 190N or more, a flexural strength of 200N or more after reheating, and a resistance of 10 or more in log form as described in the Examples below can be obtained.
[0039] In the ceramic composition of the present invention, when Fe, Cu, Zn, Mn, Co and Ni are converted into Fe2O3, CuO, ZnO, MnO, CoO and NiO respectively and the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO is set to 100 mol%, it is preferred that Fe is converted into Fe2O3 containing 44.4 mol% to 49.2 mol%, Zn is converted into ZnO containing 26.9 mol% to 33.0 mol%, and Co is converted into CoO containing 0.0004 mol% to 0.2500 mol%.
[0040] The ceramic composition of the present invention can improve the initial flexural strength, flexural strength after reheating and insulation resistance, and can improve the initial magnetic permeability and Curie temperature by making the contents of Fe, Zn and Co within the above preferred ranges. For example, a magnetic composition can be obtained with an initial flexural strength of 190N or more, a flexural strength of 200N or more after reheating, a resistance of 10 or more in log form, an initial magnetic permeability μ' of 400 or more, and a Curie temperature of 150°C or more, as described in the embodiments described later.
[0041] The ceramic composition of the present invention preferably contains 5ppm to 600ppm of Y calculated as Y2O3 relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO. The ceramic composition of the present invention can improve the flexural strength after reheating by making the content of Y within the above-mentioned preferred range. For example, a magnetic composition can be obtained in which the flexural strength after reheating is more than 210N and the strength increase rate of the initial flexural strength compared with the flexural strength after reheating is more than 110% as described in the embodiments described later. It is preferred that Y contains 50ppm to 600ppm calculated as Y2O3. The content of Y in the ceramic composition of the present invention, calculated as Y2O3, relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO, can be, for example, less than 400ppm.
[0042] The ceramic composition of the present invention preferably contains 10ppm to 600ppm of Cr calculated as Cr2O3 relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO. The ceramic composition of the present invention can further improve the flexural strength after reheating by making the Cr content within the above-mentioned preferred range. For example, a magnetic composition can be obtained in which the flexural strength after reheating is more than 210N and the strength increase rate of the initial flexural strength compared with the flexural strength after reheating is more than 110% as described in the embodiments described later. It is more preferable to contain 50ppm to 600ppm of Cr calculated as Cr2O3.
[0043] The Cr content of the ceramic composition of the present invention, calculated as Cr 2 O 3 , may be, for example, 400 ppm or less relative to 100 parts by weight of the total amount of Fe 2 O 3 , CuO, ZnO, MnO, CoO, and NiO.
[0044] In the present invention, the content of each element can be determined by analyzing the composition of the ceramic composition using inductively coupled plasma atomic emission / mass spectrometry (ICP-AES / MS).
[0045] The ceramic composition of the present invention may further contain other elements. In addition, the ceramic composition of the present invention may further contain inevitable impurities. As inevitable impurities, typical metals such as B, C, Si, S, Cl, As, Br, I, Li, Na, Mg, Al, K, Ca, Ga, Ge, Sr, Cd, In, Sn, Sb, Ba, Pb, Bi, and transition metals such as Sc, Ti, V, Nb, Mo, Pd, Ag, and Hf may be cited.
[0046] The ceramic composition of the present invention is preferably produced as follows.
[0047] First, Fe2O3, CuO, ZnO, NiO, MnO, CoO, Y2O3 and Cr2O3 are weighed so that the composition after calcination is a prescribed composition, and the raw materials are put into a ball mill together with pure water and PSZ (partially stabilized zirconia) balls, and wet mixed and crushed for a prescribed time (for example, 4 hours to 8 hours). After evaporation and drying, the pre-calcined product (pre-calcined powder) is prepared by pre-calcining at a prescribed temperature (for example, 700°C to 800°C) for a prescribed time (2 hours to 5 hours).
[0048] The obtained precalcined product (precalcined powder) was put into a ball mill together with pure water, polyvinyl alcohol as a binder, a dispersant, a plasticizer and PSZ, and mixed and pulverized in a wet manner. The slurry obtained by the mixed and pulverized was dried and granulated in a spray dryer to prepare a granular powder.
[0049] A metal mold is prepared and the prepared granular powder is pressed and molded to form a molded body.
[0050] Next, the molded body is calcined in a calcining furnace at a predetermined temperature (eg, 1000° C. to 1200° C.) for a predetermined time (eg, 2 hours to 5 hours). A ceramic composition is obtained through the above steps.
[0051] The generation of ferrite is represented by the following chemical formula, for example.
[0052] MO+Fe2O3→MFe2O4
[0053] (Here M represents metals such as Zn, Ni, Cu, Mn, Co, etc.)
[0054] By designing the ceramic composition of the present invention to intentionally contain more MO or Fe2O3 or to utilize impurities, it is possible to make it in a state where a ferrite formation reaction is easily induced during reheating, thereby repairing the scratches that serve as the starting point of cracking.
[0055] In the present invention, by further optimizing both Y2O3 acting on M of MFe2O4 and Cr2O3 acting on Fe, the flexural strength of the ceramic composition after reheating can be improved.
[0056] By making Y2O3 in the ceramic composition 5ppm to 800ppm relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO, ZnO and CuO that contribute to diffusion during subsequent reheating are captured during calcination, so that ferrite reaction is easily caused during reheating, and the strength of the ceramic composition is more easily improved. When Y2O3 exceeds 800ppm, multiple heterogeneous phases composed of unreacted substances are formed in the ferrite, forming crack starting points, and sufficient strength (initial flexural strength and flexural strength after reheating) cannot be obtained.
[0057] By making the Cr2O3 in the ceramic composition 5ppm to 800ppm relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO, the reaction of Fe2O3 during firing is suppressed and it is retained as Fe2O3 until reheating, thereby easily causing ferrite reaction during reheating and easily improving the strength. When Cr2O3 exceeds 800ppm, the spinel phase derived from Cr is generated in the ferrite and becomes the starting point of cracking, and sufficient strength (initial flexural strength and flexural strength during reheating) cannot be obtained.
[0058] The ceramic composition of the present invention is used, for example, in a ceramic core of a coil component, and is particularly preferably used in a ceramic core of a wire-wound coil component. The use of the ceramic composition of the present invention is not particularly limited, and it can also be used, for example, in a unit cell of a stacked inductor device or the like.
[0059] [Coil parts]
[0060] The coil component of the present invention includes a ceramic core composed of the ceramic composition of the present invention.
[0061] Figure 1 This is a front view schematically showing an example of the coil component of the present invention. Figure 2 To schematically represent the composition Figure 1 A perspective view of an example of a ceramic core of a coil component is shown.
[0062] Figure 1 and Figure 2 These are schematic diagrams and their dimensions, aspect ratios, and other scales may differ from those of actual products.
[0063] In the following description, terms that indicate the relationship between elements (such as "vertical", "parallel", "orthogonal", etc.) and terms that indicate the shape of an element are not expressions that have strict meanings, but are expressions that imply a practically equivalent range, for example, also including differences of several percent.
[0064] Figure 1 The coil component 10 shown is a wound coil component, and includes a ceramic core 20, a terminal electrode 50, and a conducting wire (coil) 55. The ceramic core 20 is made of the ceramic composition of the present invention.
[0065] like Figure 1 and Figure 2 As shown, the ceramic core 20 includes a winding core 30 extending in the length direction L and a pair of flanges 40 provided at opposite ends of the winding core 30 in the length direction L. The winding core 30 and the flanges 40 are integrally formed.
[0066] In this manual, Figure 1 and Figure 2 As shown in the figure, the direction in which the pair of flange portions 40 are arranged is defined as the length direction L, and the direction perpendicular to the length direction L is defined as Figure 1 and Figure 2 The up-down direction is defined as a height direction (thickness direction) T, and the direction perpendicular to both the length direction L and the height direction T is defined as a width direction W.
[0067] The winding core 30 is formed into, for example, a rectangular parallelepiped shape extending in the longitudinal direction L. The central axis of the winding core 30 extends parallel to the longitudinal direction L. The winding core 30 has a pair of main surfaces 31 and 32 facing each other in the height direction T and a pair of side surfaces 33 and 34 facing each other in the width direction W.
[0068] In this specification, the rectangular parallelepiped shape includes a rectangular parallelepiped with chamfered corners and ridges, a rectangular parallelepiped with rounded corners and ridges, etc. In addition, concavities and convexities may be formed on part or all of the main surface and the side surfaces.
[0069] A pair of flanges 40 are provided at both ends of the winding core 30 in the longitudinal direction L. Each flange 40 is formed into a thin rectangular parallelepiped shape in the longitudinal direction L. Each flange 40 is formed so as to protrude around the winding core 30 in the height direction T and the width direction W. Specifically, the planar shape of each flange 40 when viewed from the longitudinal direction L is formed so as to protrude in the height direction T and the width direction W relative to the winding core 30.
[0070] Each flange portion 40 has an inner end surface 41 facing the winding core portion 30 in the longitudinal direction L, an outer end surface 42 on the opposite side of the inner end surface 41 in the longitudinal direction L, a pair of side surfaces 43 and 44 facing each other in the width direction W, and a top surface 45 and a bottom surface 46 facing each other in the height direction T. The inner end surface 41 of one flange portion 40 is arranged to face the inner end surface 41 of the other flange portion 40.
[0071] The inner end surface 41 of each flange portion 40 is formed, for example, so that the entire surface thereof extends perpendicularly to the extension direction (here, the length direction L) of the central axis of the winding core portion 30. That is, the entire surface of the inner end surface 41 of each flange portion 40 is formed so as to extend parallel to the height direction T. However, an inclined surface may be formed on the inner end surface 41 of each flange portion 40.
[0072] like Figure 1 As shown, the terminal electrode 50 is provided at least on the bottom surface 46 of each flange portion 40. For example, when the coil component 10 is mounted on a circuit substrate, the terminal electrode 50 is electrically connected to the electrode of the circuit substrate. The terminal electrode 50 is composed of, for example, a Ni-based alloy such as nickel (Ni)-chromium (Cr), Ni-copper (Cu), silver (Ag), Cu, tin (Sn), etc.
[0073] The conductive wire 55 is wound around the winding core 30 . The conductive wire 55 has a structure in which a core wire mainly composed of a conductive material such as Cu is coated with an insulating material such as polyurethane or polyester. Both ends of the conductive wire 55 are electrically connected to the terminal electrodes 50 .
[0074] Although Figure 1 Although not shown, a plurality of terminal electrodes 50 may be provided on the bottom surface 46 of each flange portion 40. In addition, a plurality of conductive wires 55 may be wound around the winding core portion 30.
[0075] The coil component of the present invention is produced, for example, as follows.
[0076] As described in the above-mentioned "ceramic composition", the granular powder is pressurized to form a molded body. Next, the molded body is calcined in a calcining furnace at a specified temperature (for example, 1000°C to 1200°C) for a specified time (for example, 2 hours to 5 hours). The obtained sintered body is put into a drum and ground with a grinding material. Through this drum polishing, burrs are removed from the sintered body, and the outer surface of the sintered body (especially the corners and ridges) has a curved roundness. Through the above steps, a product such as Figure 2 Ceramic core shown.
[0077] Next, a terminal electrode is formed on at least the bottom surface of the flange portion of the ceramic core. For example, a conductive paste containing Ag and glass powder is applied to the bottom surface of the flange portion, and a base metal layer is formed by calcining at a specified temperature (for example, 850°C to 950°C). Then, a Ni-plated film and a Sn-plated film are sequentially formed on the base metal layer by electroplating, thereby forming an electroplated layer. Copper (Cu) may be included as a structural component of the electroplated layer. Alternatively, a metal terminal may be installed on the bottom surface of the flange portion to be used as a terminal electrode. For example, the calcining process for forming the base metal layer is equivalent to a reheating process.
[0078] Next, after the wire is wound around the winding core of the ceramic core, the end of the wire is joined to the terminal electrode by a known method such as hot pressing. Figure 1 Coil components such as the wound coil components shown.
[0079] The coil component of the present invention is not limited to the above-mentioned embodiments, and various applications and changes can be added within the scope of the present invention. As other shapes, for example, a top plate extending in the length direction L and connecting the flange portions can be provided. The conductor can use a core wire with a conductive material such as Cu as the main component and covered with an insulating material such as polyurethane and polyester. The shape of the core is not limited to a drum core, and can also be a ring core.
[0080] In the coil component of the present invention, the shape and size of the winding core of the ceramic core, the shape and size of the flange of the ceramic core, the thickness (wire diameter), the number of turns (number of turns), the cross-sectional shape of the wire and the number of wires are not particularly limited and can be appropriately changed according to the desired characteristics and installation location. In addition, the position and number of terminal electrodes can be appropriately set according to the number of wires and the purpose.
[0081] This specification discloses the following contents.
[0082] <1>
[0083] A ceramic composition comprising Fe, Cu, Zn, Mn, Co, Ni, Y and Cr, wherein when Fe, Cu, Zn, Mn, Co and Ni are converted into Fe2O3, CuO, ZnO, MnO, CoO and NiO respectively and the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO is taken as 100 mol%, Fe is converted into Fe2O3 containing 41.9 mol% to 49.2 mol%, Cu is converted into CuO containing 4.4 mol% to 7.5 mol%, Zn is converted into ZnO containing 21.9 mol% to 36.0 mol%, Mn is converted into MnO containing 0.043 mol% to 0.867 mol%, Co is converted into CoO containing 0.0004 mol% to 1.2293 mol%, and Ni is contained as the remainder,
[0084] Furthermore, relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO, Y is contained in an amount of 5 ppm to 800 ppm when converted to Y2O3, and Cr is contained in an amount of 5 ppm to 800 ppm when converted to Cr2O3.
[0085] <2>
[0086] The ceramic composition according to <1>, wherein the Fe is contained in an amount of 44.4 mol% to 49.2 mol% as Fe2O3, the Zn is contained in an amount of 26.9 mol% to 33.0 mol% as ZnO, and the Co is contained in an amount of 0.0004 mol% to 0.2500 mol% as CoO.
[0087] <3>
[0088] A ceramic composition according to <1> or <2> containing 5 ppm to 600 ppm of Y calculated as Y2O3 relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO.
[0089] <4>
[0090] The ceramic composition according to any one of <1> to <3> contains 10 ppm to 600 ppm of Cr calculated as Cr2O3 relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO.
[0091] <5>
[0092] A coil component includes a ceramic core formed of the ceramic composition according to any one of <1> to <4>.
[0093] <6>
[0094] According to the coil component described in <5>, the ceramic core includes a winding core portion extending in the length direction and a pair of flange portions provided at two opposite ends of the winding core portion in the length direction, each of the flange portions having: an inner end face facing the winding core portion in the length direction, an outer end face on the side opposite to the inner end face in the length direction, a pair of side faces opposite in the width direction, and a top face and a bottom face opposite in the height direction.
[0095] Furthermore, the flange portion of the ceramic core is provided with a terminal electrode at least on the bottom surface.
[0096] A conductive wire is wound around the winding core portion of the ceramic core, and an end portion of the conductive wire is electrically connected to the terminal electrode.
[0097] Example
[0098] Hereinafter, examples will be shown which more specifically disclose the ceramic composition of the present invention, but it should be noted that the present invention is not limited to these examples.
[0099] (Example 1)
[0100] Fe2O3, CuO, ZnO, NiO, MnO, CoO, Y2O3 and Cr2O3 were weighed so that the composition after calcination was the composition shown in Table 1, and the raw materials were put into a ball mill together with pure water and PSZ balls, and mixed and crushed in a wet manner for 4 hours. After evaporation and drying, the mixture was pre-calcined at 800°C for 2 hours to prepare a pre-calcined product.
[0101] The calcined product was put into a ball mill together with pure water, polyvinyl alcohol as a binder, a dispersant, a plasticizer and PSZ balls, and mixed and pulverized. The mixed and pulverized slurry was dried and granulated with a spray dryer to produce granular powder.
[0102] The prepared granular powder was pressure-molded to produce a molded body having the following dimensions after molding.
[0103] A single plate-shaped test piece with a length L dimension of 4.0 mm, a width W dimension of 2.0 mm, and a height T dimension of 1.5 mm; or
[0104] Ring-shaped specimen with an outer diameter of 20 mm, an inner diameter of 12 mm and a thickness of 1.5 mm.
[0105] The produced compact was calcined at 1100° C. for 2 hours. In this way, single plate-shaped samples 1 to 37 and ring-shaped samples 1 to 37 were produced.
[0106] The composition of the sintered body of each sample was analyzed by ICP-AES / MS to measure the content of each element. The results are shown in Table 1. Table 1 shows the content of each element converted into oxide.
[0107] [Initial flexural strength]
[0108] For single-plate samples 1 to 37, the flexural strength was measured by a three-point bending test using MODEL-1311VCW manufactured by AIKOH ENGINEERING, with a terminal having a 0.5 mm indenter radius lowered at a rate of 5 mm / min toward the center with a fulcrum distance of 3.2 mm. Ten samples of each were measured, and the average value is shown in Table 1 as the initial flexural strength.
[0109] [Flexural strength after reheating]
[0110] Next, the single plate samples of samples 1 to 37 were reheated at 900°C, which is the calcination temperature during electrode calcination, for 20 minutes (heating rate 10°C / min), and after cooling, the flexural strength was measured in the same manner as above. Ten samples of each were measured, and the average value is shown in Table 1 as the flexural strength after reheating.
[0111] Furthermore, the average value of the initial flexural strength and the flexural strength after reheating was compared to calculate the strength increase rate (initial flexural strength / flexural strength after reheating×100), which is shown in Table 1.
[0112] [Initial magnetic permeability μ']
[0113] The ring-shaped samples of Samples 1 to 37 were placed in a magnetic permeability measuring jig (Agilent Technologies, 16454A-s) and the initial magnetic permeability μ′ of each sample was measured at a measuring frequency of 100 kHz using an impedance analyzer (Agilent Technologies, E4990A). The results are shown in Table 1.
[0114] [Curie temperature]
[0115] The temperature characteristics of the initial magnetic permeability μ' at 100 kHz of the ring samples 1 to 37 at 25°C to 250°C were measured in 5°C increments using a thermostatic bath STH-120 manufactured by ESPEC and an LCR meter E4980 manufactured by Keysight Technologies, and the Curie temperature (°C) was calculated. The results are shown in Table 1.
[0116] [Insulation resistance]
[0117] The insulation resistance values in the thickness direction of the ring-shaped samples 1 to 37 were measured using a high resistance meter 4339B manufactured by Keysight Technologies. The results are shown in Table 1.
[0118]
[0119] In Table 1, samples marked with an * are comparative examples outside the scope of the present invention.
[0120] According to Table 1, among samples 2 to 5, 8 to 11, 14, 15, 18, 19, 22 to 24, 27 to 30 and 33 to 36 containing Fe, Cu, Zn, Mn, Co, Ni, Y and Cr in the prescribed range, a ceramic composition having an initial flexural strength of 190 N or more, a flexural strength of 200 N or more after reheating and a resistance of 10 or more in logarithm can be obtained.
[0121] In addition, for samples 2 to 4, 9, 10, 14, 15, 18, 19, 23, 24, 27 to 30 and 33 to 36, in which Fe is converted into Fe2O3 and contains 44.4 mol% to 49.2 mol%, the above-mentioned Zn is converted into ZnO and contains 26.9 mol% to 33.0 mol%, and the above-mentioned Co is converted into CoO and contains 0.0004 mol% to 0.2500 mol%, it is possible to obtain a ceramic composition having an initial flexural strength of not less than 190 N, a flexural strength after reheating of not less than 200 N, a resistance of not less than 10 in log form, an initial magnetic permeability μ' of not less than 400, and a Curie temperature of not less than 150°C.
[0122] In addition, in samples 2 to 5, 8 to 11, 14, 15, 18, 19, 22 to 24, 28 to 30 and 34 to 36, in which Y is converted to Y2O3 and contains 5 ppm to 600 ppm, and Cr is converted to Cr2O3 and contains 10 ppm to 600 ppm, a ceramic composition can be obtained in which the flexural strength after reheating is greater than 210N and the strength increase rate between the initial flexural strength and the reheated flexural strength is greater than 110%.
Claims
1. A ceramic composition comprising Fe, Cu, Zn, Mn, Co, Ni, Y and Cr, Furthermore, when Fe, Cu, Zn, Mn, Co and Ni are converted into Fe2O3, CuO, ZnO, MnO, CoO and NiO respectively and the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO is set to 100 mol%, Fe is converted into Fe2O3 containing 41.9 mol% to 49.2 mol%, Cu is converted into CuO containing 4.4 mol% to 7.5 mol%, Zn is converted into ZnO containing 21.9 mol% to 36.0 mol%, Mn is converted into MnO containing 0.043 mol% to 0.867 mol%, Co is converted into CoO containing 0.0004 mol% to 1.2293 mol%, and Ni is contained as the remainder, Relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO, 5 ppm to 800 ppm is contained when Y is converted into Y2O3, and 5 ppm to 800 ppm is contained when Cr is converted into Cr2O3.
2. The ceramic composition according to claim 1, wherein The Fe is converted into Fe2O3 and contains 44.4 mol% to 49.2 mol%, the Zn is converted into ZnO and contains 26.9 mol% to 33.0 mol%, and the Co is converted into CoO and contains 0.0004 mol% to 0.2500 mol%.
3. The ceramic composition according to claim 1, wherein Y is contained in an amount of 5 ppm to 600 ppm when converted to Y2O3, relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO.
4. The ceramic composition according to claim 1, wherein 10 ppm to 600 ppm of Cr is contained in terms of Cr2O3 relative to 100 parts by weight of the total amount of Fe2O3, CuO, ZnO, MnO, CoO and NiO. 5 . A coil component comprising a ceramic core composed of the ceramic composition according to claim 1 .
6. The coil component according to claim 5, wherein The ceramic core includes a winding core portion extending in the length direction and a pair of flange portions provided at two opposite ends of the winding core portion in the length direction, wherein each of the flange portions has: an inner end face facing the winding core portion in the length direction, an outer end side face on the opposite side to the inner end face in the length direction, a pair of side faces opposite in the width direction, and a top face and a bottom face opposite in the height direction. The flange portion of the ceramic core is provided with a terminal electrode at least on the bottom surface. A conductive wire is wound around the winding core portion of the ceramic core, and an end portion of the conductive wire is electrically connected to the terminal electrode.
Citation Information
Patent Citations
Coil device
JP2018125397A